The age of Elizabeth in the age of Johnson - Lynch, Jack (John T.) (Cambridge University Press, 2003)
"In The Age of Elizabeth in the Age of Johnson, Jack Lynch explores eighteenth-century British conceptions of the Renaissance, and the historical, intellectual, and cultural uses to which the past was put. Scholars, editors, historians, religious thinkers, linguists, and literary critics of the period all defined themselves in relation to "the last age" or "the age of Elizabeth." Seventeenth- and eighteenth-century thinkers reworked older historical schemes to suit their own needs, turning to the age of Petrarch and Poliziano, Erasmus and Scaliger, Shakespeare, Spenser, and Queen Elizabeth to define their culture in contrast to the preceding age